Determinanty umiędzynarodowienia kadry instytucji sportowych - Panfil, Ryszard (Determinants of staff internationalization in sports institutions, 2006)
The globalization of competition in the sports service market determines the dynamics of the staff internationalization process in sports organizations. The research concerns licensed players and trainers, coaches and managers in institutions engaged in basketball and football. The determinants of the process under study are divided into stimulators and regulators. The results seem to constitute interesting comparative material.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 109-118